Tuning the Tumor Myeloid Microenvironment to Fight Cancer - Jahchan, Nadine S.; Mujal, Adriana M.; Pollack, Joshua L.; Binnewies, Mikhail; Sriram, Venkataraman; Reyno, Leonard; Krummel, Matthew F. (Frontiers in Immunology, 2019)
The tumor microenvironment (TME) of diverse cancer types is often characterized by high levels of infiltrating myeloid cells including monocytes, macrophages, dendritic cells, and granulocytes. These cells perform a variety of functions in the TME, varying from of immune suppressive to immune stimulatory roles. In this review, we summarize the different myeloid cell populations in the TME and the intratumoral myeloid targeting approaches that are being clinically investigated, and discuss strategies that identify new myeloid subpopulations within the TME. The TME therapies include agents that modulate the functional activities of myeloid populations, that impact recruitment and survival of myeloid subpopulations, and that functionally reprogram or activate myeloid populations. We discuss the benefits, limitations and potential side effects of these therapeutic approaches.